«Громові стріли» з Чорнівського городища ХІІІ ст. - Калініченко, Віталій; Пивоваров, Сергій (Київ, Інститут археології НАН України, 2022)
стаття присвячена аналізу специфічних артефактів, т. зв. «стріл і сокир громових», виявлених під час археологічних досліджень Чорнівського городища ХІІІ ст. Усі ці знахідки належать до попередніх історичних епох: доба бронзи — слов’янський час. З території городища походять п’ять знахідок: кам’яна шліфована просвердлена сокира, бронзовий наконечник скіфської стріли із проробленим у втулці отвором для носіння, а також три бронзові фібули. The paper is devoted to the analysis of specific artefacts, namely so-called «arrows of thunder», which were discovered during the archaeological research of the Chornivka hillfort of the 13th century. All these finds belong to previous historical epochs since the Bronze Age to the Slavic one. The oldest of the discovered objects belongs to the Bronze Age. This is a stone axe. In its central part somewhat asymmetrically from the sides a hole is drilled. In some places, the surface of the item is chipped and scratched which indicates its use as a working tool. Stone axes of this type belong to the Bronze Age and date back to the 2nd millennium BC. They appeared among the tribes of corded pottery cultures represented in the region by the Subcarpathian local variant. The next find is a Scythian bronze arrowhead with a hole made in the socket for hanging. Arrowheads of a similar type are found in Scythian antiquities and date to the 6th century BC. Three other archaic objects from the settlement belong to the personal costume adornment. These are bronze fibulae. The first of them is a fragmented Pomeranian fibula (Eggers II type) which correlates with the antiquities of the Pojaneşti-Lukashivka culture and dates approximately to the late 2nd — the first half of the 1st century BC. The second fibula is heavily profiled, with a support plate above the string and a shortened solid receiver. It belongs to the Almgren 69 type, dating back to the second half of the 1st — the early 2nd century AD and is probably connected with the sites of the Lipitsa culture. The last of the findings refers to the Danubian — Illyrian series of cast fibulae with pseudo-returned foot and human image on the back (group E according to A. Megurianu).
«Arrows of thunder» from Chornivka hillfort of the 13th century
Keywords: археологічні дослідження; Буковина; Чорнівське городище; "громові стріли"; кам'яна сокира; наконечники стріл; фібула; пізній латен; ранньоримський час; раннє середньовіччя; середньовіччя